la televisión juega con el otro: Marcos de injusticia provocados por el experimento de televisión social "¿Qué vas a hacer?" - Sepulveda, Lucas Afonso (2020)
This article investigates two episodes of the segment Vai fazer o quê?, a social television experiment shown on the Sunday show Fantástico (TV Globo). We performed a frame analysis to understand the different meanings on the injustice represented and staged in the show’s “2013 Christmas Special” and “2016 Christmas Special.” Finally, we sought to reflect on the proposal of the social television experiment in question and what it reveals about how our television and society addresses alterity.